تعليم مهارة الكلام بمعهد تأديب الشاكرين الإسلامية: TEACHING OF SPEAKING SKILL AT TA'DIB AS-SYAKIRIN ISLAMIC BOARDING SCHOOL IN MEDAN - Maria Ulfa Lubis; Zulpina (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2021)
Abstract: This study aims to determine how the application, objectives, functions, learning methods, learning steps, material taught, supporting and inhibiting factors, as well as problems experienced by the teacher while teaching Maharah Kalam at the Ta'dib Asy-Syakirin Islamic Boarding School, Medan. . The research method used is descriptive qualitative research methods. The results showed that the learning of Maharah Kalam at the Ta'dib Asy-Syakirin Islamic Boarding School was significant in changing the behavior of students towards the learning outcomes achieved, as well as the teachers who were generally professionals. Keyword: Maharah al-Kalam, learning, Arabic Language تهدف هذه الدراسة إلى تحديد كيفية التطبيق والأهداف والوظائف وطرق وخطوات التعليم والمواد التي يتم تدريسها والعوامل الداعمة والمثبطة، بالإضافة إلى المشكلات التي يواجهها المعلم أثناء تدريس مهارة الكلام بمعهد تأديب الشاكرين الإسلامية. أما منهج البحث المستخدم هو طريقة البحث الوصفي النوعي.أظهرت النتائج أن تعليم مهارة كلام بمعهد تأديب الشاكرين الإسلامية كان مهمًا في تغيير سلوك الطلاب تجاه نتائج التعلم المحققة ، وكذلك المعلمين الذين كانوا عمومًا محترفين